4.9k views
5 votes
Inverse of f(x) = x2 − 9

User Avalanchy
by
4.6k points

2 Answers

3 votes
To find the inverse of a function, replace every x in the equation with a y, and replace every y in the equation with an x:


x = y^(2) - 9

Add 9 to both sides:


y^(2) = x + 9

Square root both sides to get y by itself:


y = √(x+9)

This equation can be simplified by taking the square root of 9 out of the root:


√(9) = 3

y = 3 + √(x)

The inverse of this function is y = 3 + √x.
User Obscure Geek
by
5.4k points
0 votes
f(x) = x2 - 9
y = x2 - 9
y - 9 = x2

√(y - 9) = x

y = f(x)
f^(-1) (y) = x
f^(-1) (y) =
√(y - 9)
f^(-1) (x) =
√(x - 9)
User Branislav
by
5.4k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.